Notable photocatalytic activity of TiO2-polyethylene nanocomposites for visible light degradation of organic pollutants - M. Romero-Saez; L. Y. Jaramillo; R. Saravanan; N. Benito; E. Pabon; E. Mosquera; F. Gracia (eXPRESS Polymer Letters)
This paper reports on the photocatalytic activity showed by nanocomposites of TiO2 with low density polyethylene (LDPE) and high density polyethylene (HDPE) (10, 20 wt%) for the degradation of methyl orange in aqueous medium under visible light irradiation. TiO2 was synthetized by sol-gel process, and the polymers were incorporated by impregnation. Both the pure TiO2 and the nanocomposites were characterized using different physico-chemical techniques including specific surface area analysis, X-ray diffraction analysis, transmission electron microscopy, ultraviolet-visible and photoluminescence spectroscopy, and X-ray photoelectron spectroscopy. All the prepared nanocomposites showed an absorption edge in the visible region. TiO2(90)/LDPE photocatalyst showed the best degradation efficiency after 180 minutes of reaction, without notorious decrease of degradation efficiency after three consecutive uses. Photoluminescence and X-ray photoelectron spectroscopy analyses suggested the presence of vacancies in the TiO2 structure promoted by a Ti–O–C interaction being responsible for the photocatalytic activity enhancement under visible light irradiation.